The Effect of Stocking Density on the Growth of Ocellaris Clownfish (Amphiprion ocellaris Cuvier, 1830) With Recirculation - Atiek Pietoyo; Kurniawan Wahyu Hidayat; Siti Nurazizah; Irvan Firmansyah Zainul Arifin; DH Guntur Prabowo; Fajar Tri Widianto; Irpan Mustakim (Department of Aquaculture, 2020)
The ornamental fish business is now an economic driver. The ocellaris clownfish (Amphiprion ocellaris Cuvier, 1830) is one of the leading commodities of marine ornamental fish that is in great demand, especially in foreign markets. One obstacle faced by farmers in determining the appropriate density for the ocellaris clownfish rearing stage. This study aimed to evaluate the effect of stocking density on production factors, which included survival rate, and growth rate of ocellaris clownfish. Three hundred fish were used as experimental fish with an average length of 23.00 ± 2.36 mm and a weight of 0.27 ± 0.02 gather study was conducted using 4 treatment tanks with a volume of 120 L with densities of 0.17, 0.37, 0.67, and 0.80 fish/L. Observations showed that the density of 0.37 fish per L (K2) gave the best results with a survival rate of 98.18%. For the SGR parameter, the highest value was 1.14% per day in the K1 treatment. This indicated that the stocking density has a relationship with the factor of production in rearing ocellaris clownfish in the recirculation system.